Perilaku Belanja Online Konsumen Selama Pandemi Covid-19 di Jawa Timur Indonesia - Rovilla Amalia; Sri Hartini (Mahesa Research Center, 2022)
The COVID-19 pandemic that has occurred has resulted in changes in people's daily routines, including shopping behavior. This study aims to provide a descriptive description of consumer behavior in online shopping activities during the COVID-19 pandemic. The type of research used is descriptive observational research. The sample in this study were users of online shopping sites during the COVID-19 pandemic in East Java, Indonesia. Samples were taken using nonprobability sampling technique with a total sample of 384 respondents. The data collection method used is a questionnaire. The result of this study is that consumer behavior in online shopping activities has increased during the COVID-19 pandemic and this behavior is influenced by the perceived benefit factor. respondents prefer shopping online as a place to shop both before and during the COVID-19 pandemic. The reason for shopping at e-commerce during the COVID-19 pandemic is because it is safer than COVID-19 distribution, saves time and provides many discount offers.